Pengaruh Kualitas Produk, Citra Merek, dan Persepsi Harga Terhadap Kepuasan Konsumen Pampers Sweety Surabaya - Shafa’Aqilah Kautsar; Mataji Mataji (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2026)
This study seeks to examine the impact of product quality, brand image, and price perception on consumer satisfaction for Sweety nappy goods in Surabaya. The competitive dynamics of the infant nappy industry, along with variations in Sweety sales, need an assessment of the elements influencing consumer satisfaction levels. The employed study strategy is a quantitative approach, utilising questionnaires distributed to Sweety consumers in the Surabaya region. Product quality factors are measured through indications of durability, reliability, conformance to standards, and simplicity of use. Brand image is assessed by identity, personality, associations, brand attitudes and behaviours, and perceived advantages. Price perception is assessed based on affordability, price competitiveness, alignment of price with product quality, and alignment of price with advantages. This study aims to deliver an empirical analysis of the primary variables affecting consumer satisfaction with Sweety, serving as a foundation for companies to enhance marketing strategies, elevate product quality, and fortify brand image in the increasingly competitive baby diaper sector. The results indicate that product quality has a positive and significant effect on consumer satisfaction, suggesting that consumers feel satisfied when baby diapers have good absorbency, soft materials, and are comfortable to use. Brand image also has a positive and significant effect, meaning that consumers’ perceptions of Sweety’s reputation and trust contribute to increased satisfaction. In contrast, price perception has a positive but insignificant effect, indicating that consumers place greater emphasis on product quality and brand trust than on price considerations. Simultaneously, product quality, brand image, and price perception significantly influence consumer satisfaction. These findings confirm that product quality and brand image are dominant factors that should be prioritized by companies to enhance consumer satisfaction and loyalty amid the growing competition in the baby diaper industry.